What if Acupuncture Were Covered by Insurance for Pain Management? A Cross-Sectional Study of Cancer Patients at One Academic Center and 11 Community Hospitals. Issue 10 (24th April 2019) - Liou, Kevin T; Hung, Tony K W; Meghani, Salimah H; Epstein, Andrew S; Li, Q Susan; Romero, Sally A D; Cohen, Roger B; Mao, Jun J
Abstract: Objective: In response to the national opioid crisis, governmental and medical organizations have called for broader insurance coverage of acupuncture to improve access to nonpharmacologic pain therapies, especially in cancer populations, where undertreatment of pain is prevalent. We evaluated whether cancer patients would be willing to use insurance-covered acupuncture for pain. Design and Setting: We conducted a cross-sectional survey of cancer patients with pain at one academic center and 11 community hospitals. Methods: We used logistic regression models to examine factors associated with willingness to use insurance-covered acupuncture for pain. Results: Among 634 cancer patients, 304 (47.9%) reported willingness to use insurance-covered acupuncture for pain. In univariate analyses, patients were more likely to report willingness if they had severe pain (odds ratio [OR] = 1.59, 95% confidence interval [CI] = 1.03–2.45) but were less likely if they were nonwhite (OR = 0.59, 95% CI = 0.39–0.90) or had only received high school education or less (OR = 0.46, 95% CI = 0.32–0.65). After adjusting for attitudes and beliefs in multivariable analyses, willingness was no longer significantly associated with education (adjusted OR [aOR] = 0.78, 95% CI = 0.50–1.21) and was more negatively associated with nonwhite race (aOR = 0.49, 95% CI = 0.29–0.84). Conclusions: Approximately one in two cancer patients was willing to use insurance-covered acupuncture for pain. Willingness was influenced by patients' attitudes and beliefs, which are potentially modifiable through counseling and education. Further research on racial disparities is needed to close the gap in utilization as acupuncture is integrated into insurance plans in response to the opioid crisis.